ANALYSIS OF THE ROLE OF THE HUMAN CAPITAL GROUPIN THE TRAVEL PROCEDURE OF PT ASURANSI JASA INDONESIA AS TOURISM SUPPORT - Ridha, Mohammad; Nggebu, Sila Fide Novira (UI Scholars Hub, 2022)
In this era of globalization, competition in all fields is increasing, requiring companies to have high competitiveness. There are various ways to advance the company, one of them by carrying out business trip activities. PT Asuransi Jasa Indonesia has SOP for business trip flows to run effectively and efficiently. The Human Capital Group is one of the work units involved and has an important role in business trip procedures. The purpose of this paper is to determine the role of the Human Capital Group in the flow of business trip procedures and determine the advantages and disadvantages as well as obstacles and solutions that exist in these procedures. The method used for data collection is the interview method to several Human Capital Group staff who play a role in business trip procedures. The author also links the role of the Human Capital Group to the theory of the function of the human resources department according to Hendry Simamora (2006) in (Sembiring, 2010, pp.9-10). Based on the results of data collection and information, it was concluded that the Human Capital Group had carried out its duties and roles well, but there were some shortcomings and obstacles in the business trip procedures. The author also provides suggestions that are expected to be useful for the company, such as system integration, use of the system through smartphones, and others.